Bioactive compounds in fermented foods: Health benefits, safety, and future perspectives - Solomon Fitsum; Gebreselema Gebreyohannes; Desta Berhe Sbhatu (Applied Food Research)
Fermentation is a vital biotechnological process that enhances food safety, nutrition, and bioactive compound production through microbial activity. Traditional fermentation relies on spontaneous microbial communities, generating diverse metabolites such as GABA and SCFAs, which support neuroprotection, gut health, and metabolic regulation. In contrast, modern fermentation employs controlled biotechnological processes to optimize bioactive compound yield and ensure product consistency and safety. While traditional methods involve complex microbial interactions that result in inconsistent bioactive profiles, industrial fermentation utilizes selected strains to maximize efficiency and standardize outcomes. However, traditional fermentation presents safety concerns, including hygiene risks and inconsistent microbial control. Standardized fermentation agents (starter cultures) mitigate these risks, improving reproducibility and safety in industrial applications. Fermented foods contain bioactive compounds that contribute to weight management, cardiovascular health, glucose and lipid regulation, and immune support. Strengthening fermentation through improved practices and starter cultures enhances its potential for producing functional foods and nutraceuticals, particularly benefiting underdeveloped regions.